Anaximander’s ’Boundless Nature’ - Couprie, Dirk L.; Kočandrle, Radim (Peitho. Examina Antiqua, 2013)
The usual interpretation has it that Anaximander made ‘the Boundless’ (τὸ ἄπειρον) the source and principle of everything. However, in the works of Aristotle, the nearest witness, no direct connection can be found between Anaximander and ‘the Boundless’. On the contrary, Aristotle says that all the physicists made something else the subject of which ἄπειρος is a predicate (Phys. 203 a 4). When we take this remark seriously, it must include Anaximander as well. This means that Anaximander did not make τὸ ἄπειρον the source or principle of everything, but rather called something else ἄπειρος. The question is, then, what was the subject that he adorned with this predicate. The hypothesis defended in this article is that it must have been ϕύσις, not in its Aristotelian technical sense, but in the pregnant sense of natura creatrix: the power that brings everything into existence and makes it grow and move. This ‘nature’ is boundless. It rules everything and in this sense it can be called ‘divine’. Being boundless, the mechanisms of nature, in which the opposites play an important role, are multifarious. The things created by boundless nature are not boundless, but finite, as they are destined to the destruction they impose onto each other, as Anaximander’s fragment says.